The Influence of Implementation of Total Quality Management and Innovation Quality Through Competitive Advantage on Company Performance (Empirical Study at Coffee Shop in Semarang) - Hudha, Nurul; Hidayati, Retno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This research aims to analyze the influence of total quality management implementation factors and innovation quality through competitive advantage to improve company performance. Sampling used a purposive sampling technique, the total sample used was 152 respondents who were coffee shop owners in Semarang which had an operational time of more than 1 year and had dine-in and takeaway services. The data analysis technique used in this research is SEM (Structural Equation Model) analysis with the AMOS program, and the data collection technique uses a questionnaire. The research results show that the implementation of quality management has a positive influence on company performance. Then the quality of innovation has a positive influence on company performance and competitive advantage fully mediates company performance.